3D bioprinted human iPSC-derived somatosensory constructs with functional and highly purified sensory neuron networks. (1st June 2021) - Hirano, Minoru; Huang, Yike; Vela Jarquin, Daniel; De la Garza Hernández, Rosakaren Ludivina; Jodat, Yasamin A; Luna Cerón, Eder; García-Rivera, Luis Enrique; Shin, Su Ryon
Abstract: Engineering three-dimensional (3D) sensible tissue constructs, along with the complex microarchitecture wiring of the sensory nervous system, has been an ongoing challenge in the tissue engineering field. By combining 3D bioprinting and human pluripotent stem cell (hPSC) technologies, sensible tissue constructs could be engineered in a rapid, precise, and controllable manner to replicate 3D microarchitectures and mechanosensory functionalities of the native sensory tissue (e.g. response to external stimuli). Here, we introduce a biofabrication approach to create complex 3D microarchitecture wirings. We develop an hPSC-sensory neuron (SN) laden bioink using highly purified and functional SN populations to 3D bioprint microarchitecture wirings that demonstrate responsiveness to warm/cold sense-inducing chemicals and mechanical stress. Specifically, we tailor a conventional differentiation strategy to our purification method by utilizing p75 cell surface marker and DAPT treatment along with neuronal growth factors in order to selectively differentiate neural crest cells into SNs. To create spatial resolution in 3D architectures and grow SNs in custom patterns and directions, an induced pluripotent stem cell (iPSC)-SN-laden gelatin bioink was printed on laminin-coated substrates using extrusion-based bioprinting technique. Then the printed constructs were covered with a collagen matrix that guided SNs growing in the printed micropattern. Using a sacrificial bioprinting technique, the iPSC-SNs were seeded into the hollow microchannels created by sacrificial gelatin ink printed in the gelatin methacryloyl supporting bath, thereby demonstrating controllability over axon guidance in curved lines up to several tens of centimeters in length on 2D substrates and in straight microchannels in 3D matrices. Therefore, this biofabrication approach could be amenable to incorporate sensible SN networks into the engineered skin equivalents, regenerative skin implants, and augmented somatosensory neuro-prosthetics that have the potential to regenerate sensible functions by connecting host neuron systems in injured areas.